2016
DOI: 10.4209/aaqr.2015.05.0295
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Characterization of Particles and Fibers Released during Abrasion of Fiber-Reinforced Composite in a Workplace Influenced by Ambient Background Sources

Abstract: We demonstrate the use of high-to low-resolution microscopy and particle chemical analysis during normal vacuum and cryo-conditions to identify the nature and relative abundances of process-generated particles and fibers from sanding of a glass and carbon fiber epoxy layer-composite in a workplace influenced by both indoor and ambient background sources. The study suggests that a proper exposure characterization requires multiple techniques covering wide size ranges to reach a conclusion. Besides a rise in num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This sampling technique has been used successfully in environmental Kandler et al, 2011;Nguyen et al, 2017), occupational (Jensen et al, 2015;Kling et al, 2016;Koivisto et al, 2018), and combustion particle studies (Lieke et al, 2013). The Micro Inertial Impactor samples particles up to ca.…”
Section: Particle Sampling and Characterizationmentioning
confidence: 99%
“…This sampling technique has been used successfully in environmental Kandler et al, 2011;Nguyen et al, 2017), occupational (Jensen et al, 2015;Kling et al, 2016;Koivisto et al, 2018), and combustion particle studies (Lieke et al, 2013). The Micro Inertial Impactor samples particles up to ca.…”
Section: Particle Sampling and Characterizationmentioning
confidence: 99%
“…Knowledge is currently developing on the process-specific particle emissions and release of fibrous nanomaterials during the life-cycle processes (e.g., sanding, weathering, shredding, and incineration) of carbon-based nanocomposites. Recently, it was shown that significant fractions of carbon fibers of μm-size diameters were clearly separated from matrix during industrial-scale grinding and sanding of layered silica-carbon epoxy composite [ 16 ]. Conversely, sanding of dispersed epoxy/CNT nanocomposite, using a smaller hand-held sander in laboratory setup produced only dust epoxy particles with protruding CNT [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon composites have become a crucial component in modern technology, with numerous applications in military, civilian, energy, medical, and environmental fields. Polymer composites, made with affordable materials and equipment, are easy to produce and offer both process ability and cost-effectiveness [5][6][7].Composite materials are produced by combining or merging different materials or qualities in which the component elements are individually distinct, or, two or more phases combined physically, which result in a new material that has excellent features if compared to the features of the individual phases [8][9][10].In opposing to alloys, every phase of composites keeps its distinguished physical, mechanical, and chemical properties [9,11,12].The essential utilities of composites are good stiffness, high specific strength, and good electrical and thermal properties results. In addition to lightweights when they are compared with alloys or ceramics products [13,14].…”
Section: Introductionmentioning
confidence: 99%